2005
DOI: 10.1523/jneurosci.4573-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor Trafficking: Endoplasmic Reticulum Quality Control Involves Ligand Binding and Receptor Function

Abstract: The glutamate receptor (GluR) agonist-binding site consists of amino acid residues in the extracellular S1 and S2 domains in the N-terminal and M3-M4 loop regions, respectively. In the present study, we sought to confirm that the conserved ligand-binding residues identified in the AMPA receptor S1S2 domains also participate in ligand binding of GluR6 kainate receptors. Amino acid substitutions were made in the GluR6 parent at R523, T690, and E738 to alter their potential interactions with ligand. Mutant recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
80
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 73 publications
17
80
1
Order By: Relevance
“…Additional stability may be provided by stargazin (and other TARPs) as part of the native complex. Considering the close structural similarity and related findings with other iGluR (Grunwald and Kaplan, 2003;Mah et al, 2005;Valluru et al, 2005), the requirement for agonist binding may be a general property of iGluR maturation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Additional stability may be provided by stargazin (and other TARPs) as part of the native complex. Considering the close structural similarity and related findings with other iGluR (Grunwald and Kaplan, 2003;Mah et al, 2005;Valluru et al, 2005), the requirement for agonist binding may be a general property of iGluR maturation.…”
Section: Discussionmentioning
confidence: 66%
“…Point mutations in the agonist-binding domain of Caenorhabditis elegans GLR-1 (Grunwald and Kaplan, 2003), mammalian kainate (Mah et al, 2005;Valluru et al, 2005;Fleck, 2006;Priel et al, 2006), and AMPA receptor subunits (Greger et al, 2006) have been reported to impede the expression of the cognate receptors on cell surface. The nature of the responsible mechanism(s) and the importance of agonist-binding activity itself, for the transport of AMPA receptors, are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…2, B and C, 5). Interestingly, binding site mutations in the kainate receptor GluK2 that abolish its function actually increased the tetramer fraction (50). We therefore tested the tetrameric stability of the receptor using the SDS approach either with or without glutamate in the solubilization buffer (data not shown), but did not observe any difference, possibly due to limited sensitivity of the assay.…”
Section: Discussionmentioning
confidence: 99%
“…AMPARs containing both GluA1 and GluA2 follow GluA1 trafficking rules and override the ER retention of GluA2. Thus, GluA1/2 heteromers rapidly traffic from the ER to the surface whereas AMPARs without GluA1 or GluA4 transit much more slowly 77,78 (Fig. 3).…”
Section: Rna Editing Ampar Assembly and Er Exitmentioning
confidence: 98%